Anti-EDAR Agonist Antibody Therapy Resolves Palate Defects in Pax9-/- Mice. (October 2017) - Jia, S.; Zhou, J.; Wee, Y.; Mikkola, M.L.; Schneider, P.; D'Souza, R.N.
To date, surgical interventions are the only means by which craniofacial anomalies can be corrected so that function, esthetics, and the sense of well-being are restored in affected individuals. Unfortunately, for patients with cleft palate—one of the most common of congenital birth defects—treatment following surgery is prolonged over a lifetime and often involves multidisciplinary regimens. Hence, there is a need to understand the molecular pathways that control palatogenesis and to translate such information for the development of noninvasive therapies that can either prevent or correct cleft palates in humans. Here, we use the well-characterized model of the Pax9 −/− mouse, which displays a consistent phenotype of a secondary cleft palate, to test a novel therapeutic. Specifically, we demonstrate that the controlled intravenous delivery of a novel mouse monoclonal antibody replacement therapy, which acts as an agonist for the ectodysplasin (Eda) pathway, can resolve cleft palate defects in Pax9 −/− embryos in utero. Such pharmacological interventions did not reverse the arrest in tooth, thymus, and parathyroid gland development, suggesting that the relationship of Pax9 to the Eda/Edar pathway is both unique and essential for palatogenesis. Expression analyses and unbiased gene expression profiling studies offer a molecular explanation for the resolution of palatal defects, showing that Eda and Edar-related genes are expressed in normal palatal tissues and that the Eda/Edar signaling pathway is downstream of Pax9 in palatogenesis. Taken together, our data uncover a unique relationship between Pax9 and the Eda/Edar signaling pathway that can be further exploited for the development of noninvasive, safe, and effective therapies for the treatment of cleft palate conditions and other single-gene disorders affecting the craniofacial complex.